(untitled) (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVE: to develop, validate the contents and verify the reliability of a risk classification protocol for an Emergency Unit. METHOD: the content validation was developed in a University Hospital in a country town located in the state of Sao Paulo and was carried out in two stages: the first with the individual assessment of specialists and the second with the meeting between the researchers and the specialists. The use of the protocol followed a specific guide. Concerning reliability, the concordance or equivalent method among observers was used. RESULTS: the protocol developed showed to have content validity and, after the suggested changes were made, there were excellent results concerning reliability. CONCLUSION: the assistance flow chart was shown to be easy to use, and facilitate the search for the complaint in each assistance priority.